UVB light upregulates prostaglandin synthases and prostaglandin receptors in mouse keratinocytes - Black, Adrienne T. (2008)
Prostaglandins belong to a class of cyclic lipid-derived mediators synthesized from arachidonic acid via COX-1, COX-2 and various prostaglandin synthases. Members of this family include prostaglandins such as PGE(2), PGF(2α), PGD(2) and PGI(2) (prostacyclin) as well as thromboxane. In the present studies we analyzed the effects of UVB on prostaglandin production and prostaglandin synthase expression in primary cultures of undifferentiated and calcium-differentiated mouse keratinocytes. Both cell types were found to constitutively synthesize PGE(2), PGD(2) and the PGD(2) metabolite PGJ(2). Twenty-four hr after treatment with UVB (25 mJ/cm(2)), production of PGE(2) and PGJ(2) increased, while PGD(2) production decreased. This was associated with increased expression of COX-2 mRNA and protein. UVB (2.5 – 25 mJ/cm(2)) also caused marked increases in mRNA expression for the prostanoid synthases PGDS, mPGES-1, mPGES-2, PGFS and PGIS, as well as expression of receptors for PGE(2) (EP1 and EP2), PGD(2) (DP and CRTH2) and prostacyclin (IP). UVB was more effective in inducing COX-2 and DP in differentiated cells and EP1 and IP in undifferentiated cells. UVB readily activated keratinocyte PI-3-kinase (PI3K)/Akt, JNK and p38 MAP signaling pathways which are known to regulate COX-2 expression. While inhibition of PI3K suppressed UVB-induced mPGES-1 and CRTH2 expression, JNK inhibition suppressed mPGES-1, PGIS, EP2 and CRTH2, and p38 kinase inhibition only suppressed EP1 and EP2. These data indicate that UVB modulates expression of prostaglandin synthases and receptors by distinct mechanisms. Moreover, both the capacity of keratinocytes to generate prostaglandins and their ability to respond to these lipid mediators are stimulated by exposure to UVB.